Effect of Glomus intraradices on root morphology, biomass production and phosphorous use efficiency of Chinese fir seedlings under low phosphorus stress - Tian, Yunlong; Xu, Jingjing; Lian, Xiaoqian; Wei, Bo; Ma, Xiangqing; Wu, Pengfei (Frontiers in Plant Science, 2023)
Introduction Available phosphorus (P) scarcity in the highly weathered soils of the subtropical forests in southern China is a serious concern. To ensure whether inoculation of arbuscular mycorrhizal fungi (AMF) with Chinese fir (Cunninghamia lanceolata) under low P stress conditions could promote its growth and P utilization capacity, an indoor pot simulation experiment was carried out with the different P supply treatments and Chinese fir seedlings as the tested material. Methods The experiment had two P supply treatments, no P supply (P0, 0 mmol·L-1 KH2PO4) and normal P supply (P1, 1.0 mmol·L-1 KH2PO4). The seedling in each P supply treatment was inoculated with Glomus intraradices (Gi), a widespread species of AMF in the natural environment, and with no AMF inoculation as a control treatment (CK). The Gi infection rate in the root system, root cortex tissue dissolution rate, root morphological indexes and biomass, whole plant P use efficiency, and root P use efficiency of Chinese fir were determined under different treatment conditions. Results and Discussion The results showed that P0 treatment significantly increased the Gi infection rate (p< 0.05). After inoculating AMF with different P supply treatments, the root cortex tissue dissolution rate was considerably enhanced. In contrast, the Chinese fir’s root length and surface area were reduced; however, the root volume did not change significantly. The average root diameter in the P0 treatment and inoculated with AMF was significantly more prominent than in the uninoculated treatment (p< 0.05). The root biomass and root-to-shoot ratio at different P supply treatments were significantly higher in the Gi infection treatment than in the CK group. Under different P supply treatments, root inoculation with Gi promoted root P use efficiency and whole plant P use efficiency. In conclusion, low P stress condition promoted the colonization of AMF in the root system, increased the dissolution of root cortex tissue, root volume, and the average diameter, and promoted root biomass accumulation and P use efficiency.